Flexural behavior of composite beams of Kagome truss and fiber-reinforced cementitious composites. (26th December 2022) - Choi, Jeong-Il; Park, Se-Eon; Kim, Yun Yong; Lee, Bang Yeon
Highlights: New composite beams of Kagome truss and FRCC are proposed. Flexural behavior of composite beams was influenced by type of FRCC. Composite beams with HD-FRCC in the tension region showed ductile behavior. Analytical results simulated overall behavior of beams with HD-FRCC well. Abstract: This paper presents an experimental and analytical study of the flexural behavior of composite beams of Kagome truss and fiber-reinforced cementitious composite (FRCC). Two types of FRCC—highly ductile (HD)-FRCC with a tensile ductility of 6.33 % and high-strength (HS)-FRCC with a compressive strength of 156.8 MPa—were designed. Three composite beams were manufactured. To investigate the flexural behavior of the beams, bending tests were performed. Test results showed that the flexural behavior of the Kagome truss composite beams was influenced by the types of FRCCs and reinforcement methods. The K-HS-HD beam reinforced at the tensile portion with HD-FRCC and at the compressive portion with HS-FRCC showed 4.5 and 4.9 times higher load-bearing capacities than those, respectively, of the K-HD and K-HS beams that were reinforced only at the tension region. While the analytical results and the experimental results were relatively consistent in the case of the beam reinforced with HD-FRCC, the analytical results were different from the experimental results in the nonlinear region in the case of the beam reinforced with HS-FRCC, due to local fracture of the material.